Lessons learnt and way forward for India to deal with violent extremism - Sharma, Basant K. (India-Nigeria, 2020)
Polarisation, dysfunctional institutions, perceived marginalisation of communities based on their identity and geographic and historical specificities are the main factors conducive to the rise of violent extremism. External and internal actors do play important role, however, deliverance of governance and redressal of grievances is cornerstone to conflict resolution. Engagament with the disaffected section of society is a stepping stone for reinegration of rebels and insurgents. It would require co-designing of new strategies and strengthening existing strategies. India has focused on winning hearts and mins, people friendly operations, employment for just force and political intervention to kick start the process of reconstruction, reconciliation and reintegration of disaffected population with the state.